EFEKTIVITAS MODUL BIMBINGAN DAN KONSELING BERBASIS HANDBOOK TERHADAP PROKRASTINASI AKADEMIK SISWA KELAS XI SMAN 1 SAGULING - Fauzi, Syahrul Ahmad; Hendriana, Heris; Rezza Septian, Muhammad (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
Procrastination is often experienced by teenagers. Procrastination in adolescents is caused by several factors such as wasting time, avoiding tasks, and blaming others. This study aims to determine the effectiveness of the module on academic procrastination of class XI students of SMAN 1 Saguling. The subjects in this study were 30 students of class XI and were selected based on the recommendation of the guidance and counseling teacher on the consideration of the highest level of students experiencing procrastination. Data analysis used normality test and t test. The trial process for the handbook based guidance and counseling module was carried out by distributing pretest and posttest questionnaires, calculating the effectiveness using SPSS and carried out 2 times, namely normality test and T-test on pretest and protest during the trial. The results of the normality test showed the significance value of the pretest was 0.111 and the posttest was 0.008 so that the normality test can be said to be normally distributed. The results of the t-test showed a 2-tailed significance value of 0.000 so that in this t-test there was a difference between the pretest and posttest variables because they had a 2-tailed significance value 0.05. So that the results of the t-test carried out can be seen that the developed module is proven to be effective on academic procrastination of class XI students of SMAN 1 Saguling.